Dual-Wavelength Holmium-Doped Fiber Laser Pumped by Thulium–Ytterbium Co-Doped Fiber Laser. (May 2016) - Latiff, A. A.; Dhar, A.; Harun, S. W.; Babar, I. M.; Das, S.; Paul, M. C.; Ahmad, H.
Abstract : We present an all-fiber dual-wavelength holmium-doped fiber laser operating in 2μm region using a newly developed holmium-doped fiber (HDF) as a gain medium. The proposed fiber laser is constructed by using a hybrid gain medium, i.e., a thulium–ytterbium co-doped fiber (TYDF) and an HDF in conjunction with a simple half-opened linear cavity, which is formed by a broadband mirror and an output coupler reflector. Without the HDF, the TYDF laser operates at wavelengths of 1991 and 1999 nm with a signal-to-noise ratio of more than 34 dB and the slope efficiency of 26.16 %. With the HDF, dual-wavelength output lines are obtained at 2075 and 2083nm with signal-to-noise ratios of more than 17dB, 3 dB bandwidth of less than 0.2 nm and the power difference between the two peaks of less than 1 dB at the TYDF laser pump power of 320 mW.